Assisting The Culture of Vannamei Shrimp (Litopenaeus vannamei) Biofloc Tarpaulin Pool System in Daarul Hasanah Balunijuk Islamic Boarding School, Bangka Belitung (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Fishery culture activity, by raising vannamei shrimp conducted by the Daarul Hasanah Islamic Boarding School at Balunijuk Village, is one of the blue economy concept applications. This community service activity was aimed at transferring knowledge dealing with vanname shrimp culture to Daarul Hasanah Islamic Boarding School. It is being carried out from March to October 2022 consisting of culture preparation, shrimp farming, feeding process, and pool water quality monitoring. This shrimp culture is located in a tarpaulin bioflock tank in the surrounding yard area of Daarul Hasanah Islamic Boarding School at Balunijuk Village, Bangka Belitung Province. A participatory method is delivered to emphasize the role and participation of the school administrator as participants in culturing the vannamei shrimp through a bioflock system using Probio_FmUBB technology. Results obtained during this activity indicate that participants are directed to be good manners of entrepreneurs. Furthermore, the knowledge transfer of farming the vannamei shrimp using a bioflock system can upgrade the knowledge of teachers (ustads) or the boarding school administrators. Participants are expressed to be skilled in preparing to build a 3-m rounded tank, making bioflock, stocking the shrimp fry process, farming the shrimps using a bioflock system with Probio_FmUBB technology, transporting seawater, operating electrical Genset, measuring and controlling water quality, and understanding feeding technique and theoretical knowledge of shrimp harvest. That knowledge enables to support of soft skills of students and teachers to stimulate new business for the boarding school.